Teamwork in Healthcare - Firstenberg, Michael S.; Stawicki, Stanislaw P. (IntechOpen, 2021)
One of the most important advances in the delivery of healthcare has been recognition of the need for developing highly functioning multi-disciplinary teams. Such teams, when structured in a cohesive fashion, can function more effectively and efficiently than the sum of their parts. The benefits of teamwork extend from the delivery of care to a single patient to the overall structure and function of entire care delivery systems. Recognizing the value of collaborative approaches for improving all aspects of healthcare delivery and having champions, leaders, structure, function, goals, and accountability are paramount to success, regardless of how defined. Another important pillar of teamwork is excellent communication with clearly defined information flows and cross-verification mechanisms. This book outlines how to work together for shared goals in a complex, diverse, and constantly evolving health care system.